Entrepreneurial Competencies and Networks: A Qualitative Study - Puteri Fadzline, Muhamad Tamyez; Nazaruddin, Ishal; Juhary, Ali (IRMM, 2016)
Achieving success is a highly critical issue for the small size construction firms in order to survive and grow in competitive and hostile business environments. There has been little research directed toward understanding how small and medium entreprises specifically the construction industry could systematically achieve entrepreneurial success with a synergy of competency and network. The objective of this research was to analyze the effects of entrepreneurial competency and entrepreneurial networks on small sized construction firms in Malaysia. Through in-depth interviews, salient dimensions of the competencies emerged. Entrepreneurial competency can be categorized as personal competency, strategic management competency, learning competency, opportunity competency, social network and inter-organization network as main themes. In addition, social and inter-organizational networks pursue to a better success as compared to firms that own business networks. Therefore this creates a new contribution by establishing a framework on research concepts and proposes a model of integration between these constructs and their relationships.